Importance of carcinoma-associated fibroblast-derived proteins in clinical oncology. Issue 12 (18th August 2014) - Valcz, Gabor; Sipos, Ferenc; Tulassay, Zsolt; Molnar, Bela; Yagi, Yukako
Abstract : Carcinoma-associated fibroblast (CAF) as prominent cell type of the tumour microenvironment has complex interaction with both the cancer cells and other non-neoplastic surrounding cells. The CAF-derived regulators and extracellular matrix proteins can support cancer progression by providing a protective microenvironment for the cancer cells via reduction of chemotherapy sensitivity. On the other hand, these proteins may act as powerful prognostic markers as well as potential targets of anticancer therapy. In this review, we summarise the clinical importance of the major CAF-derived signals influencing tumour behaviour and determining the outcome of chemotherapy.